Efficient Thermal Energy Management of Hollow Pin Fin Heat Sinks with and without Phase Change Material. Issue 1 (December 2021) - Ong, K. S.; Lim, C.H.; Munusamy, Y.; Choo, K.C.; Chai, G. J.; Saii, Patmashini; Naghavi, S.
Abstract: Electronic devices need to be cooled efficiently. Phase change material (PCM) could be incorporated into a conventional fin heat sink (FHS) for such a purpose. This paper reports experimental results obtained on the thermal performances of four FHSs fabricated with different arrays and numbers of hollow aluminium pin fins with various lengths and diameters. Tests were conducted with and without filling them with PCM. Heat input was kept on for 2 hours and varied from 1W, 5W and 10W. Transient heating surface temperatures were recorded on a data logger and plotted every 5 minutes. The results showed that the PCM-filled FHS resulted in faster cooling rates and lower heating surface temperatures. Long and large diameter pins performed better than small and short pins. Efficient fin heat sinks for electronic cooling are essential in view of the weight and size of the component. Hence the findings of this paper would be beneficial for electronic cooling and useful to the electronic industry for efficient thermal energy management.